The impact of innovation framework conditions on corporate digital technology integration: institutions as facilitators for sustainable digital transformation - Ionescu, Alina Măriuca; Clipa, Anca-Maria; Turnea, Elena-Sabina; Clipa, Cătălin-Ioan; Bedrule-Grigoruță, Maria Viorica; Roth, Steffen (Journal of Business Economics and Management, 2022)
This article is concerned with the impact of corporate digitalization on the corporate sustainability performance and with barriers and supportive institutional frameworks for corporate digital technology adaptation. Collected from big data sets such as the Digital Economy and Society Index (DESI) country reports and the Global Innovation Index (GII), our study draws on data from 29 European countries. A series of multiple linear regressions was run to select the most relevant predictors of corporate digital technology adaptation. The results suggest that Rule of Law, Government Effectiveness and Ease of Starting a Business are the institutional framework pillars that best predict corporate digital technology adaptation levels. Our findings further show that high levels of corporate digital technology adaptation occur where institutional frameworks are well-integrated across several social domains (economy, politics, legal system, etc.). We conclude by highlighting implications for the design of digital policies aiming at a strategic integration of digital technology adaptation and corporate sustainability. First published online 14 June 2022